1997
DOI: 10.1074/jbc.272.44.27635
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants in AUF1 Required for High Affinity Binding to A + U-rich Elements

Abstract: AUF1 is an RNA-binding protein that contains two nonidentical RNA recognition motifs (RRMs). AUF1 binds to A ؉ U-rich elements (AREs) with high affinity. The binding of AUF1 to AREs is believed to serve as a signal to an mRNA-processing pathway that degrades mRNAs encoding many cytokines, oncoproteins, and G protein-coupled receptors. Because the ARE binding activity of AUF1 appears central to the regulation of many important genes, we analyzed the domains of the protein that are important for this activity. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 39 publications
9
86
3
Order By: Relevance
“…Moreover, these residues were involved in structure stability of the free protein (23). In heterogeneous nuclear RNP-D, the C-terminal of RRM2 was important in conferring high affinity for ARE binding (24). This phenomenon suggests that those residues A, GST pull-down assay between GST or GST-TcPABP1 and TcUBP-1 or TcUBP-2 proteins, in the absence of RNA.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, these residues were involved in structure stability of the free protein (23). In heterogeneous nuclear RNP-D, the C-terminal of RRM2 was important in conferring high affinity for ARE binding (24). This phenomenon suggests that those residues A, GST pull-down assay between GST or GST-TcPABP1 and TcUBP-1 or TcUBP-2 proteins, in the absence of RNA.…”
Section: Discussionmentioning
confidence: 98%
“…Its role in regulating the half-life of mRNA species containing an AU-rich element is well characterized [3,4]. Although it is more abundant in the nucleus than in the cytoplasm [30], no nuclear function has been assigned to hnRNP D0.…”
Section: Discussionmentioning
confidence: 99%
“…The human and murine proteins are 97 % identical, suggesting an evolutionarily conserved function for hnRNP D0 [2]. hnRNP D0 has been implicated in the regulation of mRNA stability by recognizing AU-rich elements present in the 3h untranslated region of several mRNA species [3,4], and also binds the telomeric repeat and the 3h splice site sequence [5]. The B isoform of hnRNP D0 recognizes a motif in the promoter region of the human complement receptor 2 (CR2) gene [6] and co-precipitates with the TATAbinding protein (TBP), suggesting that it may represent a transcription factor [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the alternative exons can change the speci®city and/or a nity of AUF1 isoforms for AREs (Kajita et al, 1995;Wagner et al, 1997), it was important to determine whether the respective mRNAs showed identical or distinct patterns of expression. For this purpose, we designed speci®c probes for each AUF1 mRNA category (see Materials and methods and Figure 4a) and used them in S1 nuclease analysis.…”
Section: Distribution Of Auf1 Mrna Variantsmentioning
confidence: 99%